Optimized propulsor retrofit for slow steaming for a post pan-max container vessel - Will, Johannes; Greitsch, Lars (Volume 2: CFD and VIV, 2014)
Ships are typically designed for a life cycle of about 20-25 years, with a specific transportation task, that suits the instant or estimated requirements of the owner or operator. Anyhow the business model might change due to a multitude of reasons and force the owner to buy new ships or modify the existing. Such an event took place in the year 2008 with the beginning of the financial crisis and the resulting recession, which lead to a drastic decrease of the global volume of cargo. This paper describes the re-design of the propulsion system of an existing post panmax container vessel to suit the new economical boundary conditions.